Characterization of Salt-Induced Epigenetic Segregation by Genome-Wide Loss of Heterozygosity and its Association with Salt Tolerance in Rice (Oryza sativa L.) - Li, Min; Wang, Wen-Sheng; Pang, Yun-Long; Domingo, Jessica R.; Ali, Jauhar; Xu, Jian-Long; Fu, Bin-Ying; Venus, Elec B.; Li, Zhi-Kang (Frontiers in Plant Science, 2017)
In a breeding effort to develop salt tolerant (ST) rice varieties by designed QTL pyramiding, large numbers of progenies derived from 4 crosses between salt- or drought- tolerant BC2F5 IR64 introgression lines, were subjected to severe salt stress, resulting in 422 ST plants. The progeny testing of the selected F3 lines under more severe salt stress resulted in identification of 16 promising homozygous lines with high levels of ST. Genetic characterization of the 422 ST F3 progeny and 318 random F2 plants from the same 4 crosses using 105 all segregating SSR markers lead to three interesting discoveries: (1) salt stress can induce genome-wide epigenetic segregation (ES) characterized by complete loss of heterozygosity (LOH) and nearly complete loss of an allele (LOA) in the F3 progenies of 4 rice populations in a single generation; (2) ~25% of the stress induced ES loci were transgenerational and inherited from their salt- and drought- selected parents; and (3) the salt-induced LOH and LOA loci (regions) appeared to contain genes/alleles associated with ST and/or drought tolerance. 32 genomic regions that showed one or more types of salt-induced ES in the random and salt-selected progenies from these crosses. The same or different types of ES were detected with two large genomic regions on chromosomes 1 and 6 where more and the strongest ES were found across different populations. 14 genomic regions were found where the salt-induced ES regions were overlapping with QTL affecting ST related traits. The discovery of the three types of salt-induced ES showed several interesting characteristics and had important implications in evolution and future breeding for developing stress-resilient rice and crops. This salt-induced LOH and LOA were inferred to have resulted from the stress-induced gametic selection favoring one of the parental alleles in the salt-stressed F2 plants through epigenetic mechanisms such as stress induced site-specific genome-wide DNA methylation or genomic imprinting, which remains to be elucidated at the molecular level.